Self-narrative profiles of elite athletes and comparisons on psychological well-being - Houltberg, B. J.; Wang, K. T.; Qi, W.; Nelson, C. S. (Research Quarterly for Exercise and Sport, 2018)
Further research is needed on factors related to the emotional health of elite athletes. Previous research has linked self-narratives of people or their narrative identities to their psychological well-being. However, no study has yet examined self-narratives among elite athletes. Purpose: This study examined whether specific profiles or narrative identities of athletes emerge through multiple self-narrative indicators; these profiles were compared on measures of psychological well-being (e.g., depression, anxiety, postfailure shame levels, and life satisfaction). Method: Self-report data were collected from a sample of elite athletes (n = 99, Mdn age = 22 years, 52% male, 53% individual sports) competing at a National Collegiate Athletic Association Division 1, professional, or Olympic level. Results: Latent profile analysis revealed 3 profile types that significantly differed on measures of psychological well-being. Athletes with a performance-based narrative identity (high perfectionism, fear of failure, and contingent self-worth) demonstrated the highest levels of psychological disruptions (highest levels of depression, anxiety, and shame; lowest levels of life satisfaction), whereas a purpose-based narrative identity (high purpose, global self-worth, positive view of self after sport) was associated with the highest level of psychological well-being (lowest levels of depression, anxiety, and shame; highest levels of life satisfaction). Athletes in the mixed-type profile class reported better psychological well-being compared with the performance-based profile class but not the purpose-based profile class. Conclusions: Our findings provide initial evidence that particular self-narrative profiles of elite athletes contribute to their own psychological well-being in a significant way. Possible implications for practitioners are also discussed.